Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the quadratic equation [tex]\(2x^2 + 2x = 9\)[/tex], we first need to rewrite it in standard form [tex]\(ax^2 + bx + c = 0\)[/tex].
Starting from:
[tex]\[ 2x^2 + 2x = 9 \][/tex]
Subtract 9 from both sides to obtain:
[tex]\[ 2x^2 + 2x - 9 = 0 \][/tex]
Here, the coefficients are [tex]\(a = 2\)[/tex], [tex]\(b = 2\)[/tex], and [tex]\(c = -9\)[/tex].
We will use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
First, calculate the discriminant, [tex]\(\Delta\)[/tex]:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = 2^2 - 4(2)(-9) \][/tex]
[tex]\[ \Delta = 4 + 72 \][/tex]
[tex]\[ \Delta = 76 \][/tex]
Since the discriminant is positive, we will have two distinct real roots.
Next, we find the two solutions using the quadratic formula:
For [tex]\( x_1 \)[/tex]:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_1 = \frac{-2 + \sqrt{76}}{2(2)} \][/tex]
[tex]\[ x_1 = \frac{-2 + \sqrt{76}}{4} \][/tex]
[tex]\[ x_1 \approx \frac{-2 + 8.72}{4} \][/tex]
[tex]\[ x_1 \approx \frac{6.72}{4} \][/tex]
[tex]\[ x_1 \approx 1.68 \][/tex]
For [tex]\( x_2 \)[/tex]:
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_2 = \frac{-2 - \sqrt{76}}{2(2)} \][/tex]
[tex]\[ x_2 = \frac{-2 - 8.72}{4} \][/tex]
[tex]\[ x_2 \approx \frac{-10.72}{4} \][/tex]
[tex]\[ x_2 \approx -2.68 \][/tex]
Thus, the solutions to the quadratic equation [tex]\(2x^2 + 2x - 9 = 0\)[/tex] are:
[tex]\[ x \approx 1.68, -2.68 \][/tex]
These results are rounded to the nearest hundredth.
Starting from:
[tex]\[ 2x^2 + 2x = 9 \][/tex]
Subtract 9 from both sides to obtain:
[tex]\[ 2x^2 + 2x - 9 = 0 \][/tex]
Here, the coefficients are [tex]\(a = 2\)[/tex], [tex]\(b = 2\)[/tex], and [tex]\(c = -9\)[/tex].
We will use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
First, calculate the discriminant, [tex]\(\Delta\)[/tex]:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = 2^2 - 4(2)(-9) \][/tex]
[tex]\[ \Delta = 4 + 72 \][/tex]
[tex]\[ \Delta = 76 \][/tex]
Since the discriminant is positive, we will have two distinct real roots.
Next, we find the two solutions using the quadratic formula:
For [tex]\( x_1 \)[/tex]:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_1 = \frac{-2 + \sqrt{76}}{2(2)} \][/tex]
[tex]\[ x_1 = \frac{-2 + \sqrt{76}}{4} \][/tex]
[tex]\[ x_1 \approx \frac{-2 + 8.72}{4} \][/tex]
[tex]\[ x_1 \approx \frac{6.72}{4} \][/tex]
[tex]\[ x_1 \approx 1.68 \][/tex]
For [tex]\( x_2 \)[/tex]:
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_2 = \frac{-2 - \sqrt{76}}{2(2)} \][/tex]
[tex]\[ x_2 = \frac{-2 - 8.72}{4} \][/tex]
[tex]\[ x_2 \approx \frac{-10.72}{4} \][/tex]
[tex]\[ x_2 \approx -2.68 \][/tex]
Thus, the solutions to the quadratic equation [tex]\(2x^2 + 2x - 9 = 0\)[/tex] are:
[tex]\[ x \approx 1.68, -2.68 \][/tex]
These results are rounded to the nearest hundredth.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.